A kind of strong and tough self-protection flux-cored welding wire and preparation method thereof

By preparing a strong self -protective drug core welding wire, the combination of multi -base group modified carbon fiber and other materials can be used to solve the problem that the existing welding wire is difficult to meet the high strength and high toughness at the same time, and the welding efficiency and quality are improved.

CN118768800BActive Publication Date: 2025-01-24JIANGSU JIUZHOU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411042569.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-01-24
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Existing self-protected flux-core welding wires are difficult to meet the needs of high strength and high toughness at the same time, resulting in low welding efficiency and unstable weld quality.

Method used

By mixing iron powder, nickel powder, chromium powder, polyanomyal group modified carbon fiber, gold red stone, molybdenum powder, marble, and titanium dioxide, and dried by ball mill and spray drying It is filled into the U -shaped steel belt and passes through the pull -to -reduction diameter to get the welding wire.

Benefits of technology

This welding wire has excellent strong toughness and self -protection performance, can improve welding efficiency, improve the quality of welds, meet various welding requirements, and apply welding of various metal materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118768800B_ABST
    Figure CN118768800B_ABST
Patent Text Reader

Abstract

The invention relates to the field of flux-cored welding wires, and in particular to a strong and tough self-shielded flux-cored welding wire and a preparation method thereof, which are used to solve the problem that the existing self-shielded flux-cored welding wires are often difficult to simultaneously meet the requirements of high strength and high toughness; in the preparation method, the formula and preparation process of the flux-cored composition are optimized, and multi-group modified carbon fibers are added to the formula, so that the flux-cored welding wire has excellent strength, toughness and self-protection performance, and can meet various welding requirements; the flux-cored welding wire has good welding processability, can reduce the generation of defects such as pores and slag inclusions, and improve the quality stability of welds; the flux-cored welding wire is suitable for welding various metal materials, such as carbon steel, low alloy steel, stainless steel, etc., and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flux-cored welding wires, and in particular to a strong and tough self-shielded flux-cored welding wire and a preparation method thereof. Background Art

[0002] With the popularization of welding automation, the proportion of welding rods in commonly used welding materials has gradually decreased, and the proportion of flux-cored welding wires has increased year by year. Self-shielded flux-cored welding wires, with their convenience and high efficiency, can form qualified welding joints without the addition of external shielding gas, and are used for welding in the fields of low-alloy structural steel, ultra-high-strength steel, and wear-resistant surfacing. However, traditional self-shielded flux-cored welding wires have some problems in the welding process, such as low welding efficiency and unstable weld quality. In addition, some high-strength steel welding structures have high requirements for the toughness of the weld metal, and flux-cored welding wires under the prior art are often difficult to meet the requirements of high strength and high toughness at the same time. In order to solve these problems, the present invention proposes a strong and tough self-shielded flux-cored welding wire and a preparation method thereof, which aims to improve welding efficiency, improve weld quality, and enhance the toughness of the welding wire, which has important practical significance. Summary of the invention

[0003] In order to overcome the above technical problems, the purpose of the present invention is to provide a strong and tough self-shielded flux-cored welding wire and a preparation method thereof, which solves the problem that the existing self-shielded flux-cored welding wire is often difficult to simultaneously meet the requirements of high strength and high toughness.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A strong and tough self-shielded flux-cored welding wire, comprising welding wire powder;

[0006] Wherein, the welding wire powder comprises the following components in parts by weight:

[0007] 27-33 parts of iron powder, 22-28 parts of nickel powder, 11-17 parts of chromium powder, 7-19 parts of multi-group modified carbon fiber, 5-11 parts of rutile, 4-8 parts of molybdenum powder, 3-7 parts of marble and 1-5 parts of titanium dioxide;

[0008] Wherein, the multi-group modified carbon fiber is prepared by the following steps:

[0009] Step s1: adding carbon fiber to anhydrous ethanol, and then ultrasonically dispersing for 8-10 hours at an ultrasonic power of 300-350W, and then vacuum filtering, adding the filter cake to a three-necked flask equipped with a thermometer and a stirrer, and then adding sodium hydroxide solution and stirring the reaction for 1-1.5 hours at a temperature of 60-65°C and a stirring rate of 400-500r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven, and dried at a temperature of 90-95°C for 2-3 hours to obtain pretreated carbon fiber;

[0010] Step s2: adding the pretreated carbon fiber, glucose and deionized water into a three-necked flask equipped with a thermometer and a stirrer, and then stirring the reaction at a temperature of 35-40°C and a stirring rate of 400-500r / min for 10-15h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 90-95°C for 10-12h to obtain soaked carbon fiber;

[0011] Step s3: Evenly mix the soaked carbon fiber, silicon powder, nickel nitrate powder and ferric chloride powder, then add them into a graphite crucible, then place them in a tubular furnace, introduce argon protection, and sinter them at a temperature of 1400-1500°C for 1-1.5h, then cool them with the furnace, then add them into distilled water, then ultrasonically disperse them at an ultrasonic power of 300-350W for 20-30min, then vacuum filter, place the filter cake in a vacuum drying oven, and dry them at a temperature of 80-85°C for 4-5h to obtain silicon carbide coated carbon fiber;

[0012] Step s4: Add silicon carbide coated carbon fiber, silane coupling agent KH-560 and ethanol solution to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then add and heat to reflux and continue stirring and reacting for 3-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, and the filter cake is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven, and dried at a temperature of 60-65°C for 3-5 hours to obtain silicone modified carbon fiber;

[0013] Step s5: Add organosilicon modified carbon fiber, benzyltriethylammonium chloride, citric acid and deionized water into a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min. Then add and heat to reflux and continue stirring the reaction for 6-8 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 40-45°C for 5-6 hours to obtain multi-group modified carbon fiber.

[0014] As a further solution of the present invention: the usage ratio of the carbon fiber, anhydrous ethanol and sodium hydroxide solution in step s1 is 5g:60-65mL:60-65mL.

[0015] As a further solution of the present invention: the length of the carbon fiber in step s1 is 3 mm, the diameter is 5 μm, and the mass fraction of the sodium hydroxide solution is 10-15%.

[0016] As a further solution of the present invention: the dosage ratio of the pretreated carbon fiber, glucose and deionized water in step s2 is 2g:9-12g:50-55mL.

[0017] As a further solution of the present invention: the usage ratio of the soaked carbon fiber, silicon powder, nickel nitrate powder and ferric chloride powder in step s3 is 2g:6.5-7g:0.5-0.6g:0.5-0.6g.

[0018] As a further solution of the present invention: the usage ratio of the silicon carbide coated carbon fiber, the silane coupling agent KH-560 and the ethanol solution in step s4 is 2g:1.3-3.9g:50-55mL.

[0019] As a further solution of the present invention: the volume fraction of the ethanol solution in step s4 is 85-90%.

[0020] As a further solution of the present invention: the usage ratio of the organosilicon-modified carbon fiber, benzyltriethylammonium chloride, citric acid and deionized water in step s5 is 5g: 0.3-0.9g: 2.5-4.9g: 70-80mL.

[0021] As a further solution of the present invention: a method for preparing a strong and tough self-shielded flux-cored welding wire comprises the following steps:

[0022] Step 1: Evenly mix iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain mixed powder;

[0023] Step 2: Add the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:6-8, and ball mill for 3-5 hours at a ball milling rate of 400-500 r / min to obtain a ball milling slurry, and spray dry the ball milling slurry to obtain welding wire powder;

[0024] Step 3: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0025] Step 4: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 25-30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0026] Beneficial effects of the present invention:

[0027] The invention discloses a strong and tough self-shielding flux-cored welding wire and a preparation method thereof. The mixed powder is obtained by uniformly mixing iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide, the mixed powder and anhydrous ethanol are added to a ball mill for ball milling to obtain ball milling slurry, the ball milling slurry is spray-dried to obtain welding wire powder, a low-carbon steel strip is rolled to obtain a U-shaped steel strip, and the welding wire powder is filled into the U-shaped steel strip, and then the strip is closed and reduced in diameter by drawing to obtain the strong and tough self-shielding flux-cored welding wire. In the preparation method, the formula and preparation process of the flux-cored composition are optimized, and multi-group modified carbon fiber is added to the formula, so that the flux-cored welding wire has excellent strength and toughness and self-protection performance, and can meet various welding requirements. The flux-cored welding wire has good welding processability, can reduce the generation of defects such as pores and slag inclusions, and improve the quality stability of the weld. The flux-cored welding wire is suitable for welding various metal materials, such as carbon steel, low alloy steel, stainless steel, etc., and has broad application prospects.

[0028] In the process of preparing the flux-cored welding wire, a multi-group modified carbon fiber is first prepared. First, the carbon fiber is treated with anhydrous ethanol and sodium hydroxide solution in sequence to effectively remove impurities on its surface to obtain a pretreated carbon fiber. Then, the pretreated carbon fiber is immersed in a glucose solution to make glucose adhere to its surface to obtain a soaked carbon fiber. Then, the soaked carbon fiber, silicon powder, nickel nitrate powder and ferric chloride powder are mixed and sintered. Silicon carbide is prepared by using glucose as a carbon source, silicon powder as a silicon source, nickel nitrate and ferric chloride as catalysts to coat the carbon fiber to form a composite structure to obtain a silicon carbide-coated carbon fiber. Then, a silane coupling agent is used to coat the carbon fiber. KH-560 is used to treat silicon carbide coated carbon fiber. The siloxane on the silane coupling agent KH-560 is hydrolyzed to form silanol, which is then dehydrated, condensed and grafted onto the surface of the silicon carbide coated carbon fiber. At the same time, epoxy groups are introduced to obtain organosilicon modified carbon fiber. Then, citric acid is used to treat the organosilicon modified carbon fiber. The epoxy groups on the organosilicon modified carbon fiber can react with the carboxyl and hydroxyl groups on the citric acid, thereby introducing a large number of carboxyl and hydroxyl groups on the surface of the carbon fiber to obtain multi-group modified carbon fiber. Carbon fiber has good mechanical properties. After adding it to the flux-cored welding wire, it can be used as a toughening phase, so that when the matrix is ​​subjected to external impact, the toughening The tough phase can absorb most of the energy and improve the toughness of the weld. In addition, carbon fiber has good electrical and thermal conductivity, which can improve the wire feeding performance of the welding wire and the stability of the welding arc, which helps to achieve a smoother and more reliable welding process, reduce welding defects and improve welding quality. Silicon carbide is a high-hardness, high-wear-resistant material. Adding it to flux-cored welding wire can increase the hardness and wear resistance of the weld. Therefore, the composite structure of carbon fiber and silicon carbide added to flux-cored welding wire can enhance the stability and thermal cracking resistance of the weld at high temperatures, and improve the mechanical properties of the weld such as tensile strength, yield strength and impact toughness, which makes the weld It can withstand greater loads and impacts, improve the overall performance of the welded structure, and after being modified with organic silicon, the active functional groups on the surface of the composite structure of carbon fiber and silicon carbide are increased, making it easier to further introduce a large number of carboxyl groups and hydroxyl groups, so that other welding wire powder components can be wrapped during the ball milling process, so that the surface reaches a saturated state, avoiding agglomeration, promoting the ball milling effect, and making the welding wire powder fully refined, thereby enhancing the bonding strength between the components. In addition, during the welding process, silicon carbide will be oxidized by the ferrous oxide produced by welding, that is, the following reaction occurs: SiC+3(Fe02)→3Fe+Si02+ C0. At the same time, the free carbon in silicon carbide also participates in the deoxidation reaction at high temperature: C+Fe0→Fe+C0. Studies have shown that the increase in oxygen content will lead to an increase in the grain size of the deposited metal, an increase in the content of granular bainite, an increase in the size and content of inclusions, and a significant decrease in the impact toughness of the deposited metal. The addition of silicon carbide will reduce the FeO content. As the FeO content decreases, the oxygen content in the weld deposited metal continues to decrease, which improves the toughness of the weld. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] This embodiment is a method for preparing a tough self-shielded flux-cored welding wire, comprising the following steps:

[0032] Step T1: 5 g of carbon fiber with a length of 3 mm and a diameter of 5 μm was added to 60 mL of anhydrous ethanol, and then ultrasonically dispersed for 8 h under an ultrasonic power of 300 W, and then vacuum filtered. The filter cake was added to a three-necked flask equipped with a thermometer and a stirrer, and then 60 mL of a 10% sodium hydroxide solution was added and stirred for 1 h at a temperature of 60 ° C and a stirring rate of 400 r / min. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 90 ° C for 2 h to obtain pretreated carbon fiber;

[0033] Step T2: 2 g of pretreated carbon fiber, 9 g of glucose and 50 mL of deionized water were added to a three-necked flask equipped with a thermometer and a stirrer, and then stirred for 10 h at a temperature of 35 ° C and a stirring rate of 400 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 90 ° C for 10 h to obtain soaked carbon fiber;

[0034] Step T3: 2g soaked carbon fiber, 6.5g silicon powder, 0.5g nickel nitrate powder and 0.5g ferric chloride powder were mixed evenly, and then added to a graphite crucible, and then placed in a tubular furnace, argon protection was introduced, and sintered at a temperature of 1400°C for 1h, and then cooled with the furnace, and then added to distilled water, and then ultrasonically dispersed at an ultrasonic power of 300W for 20min, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven, and dried at a temperature of 80°C for 4h to obtain silicon carbide coated carbon fiber;

[0035] Step T4: 2 g of silicon carbide coated carbon fiber, 1.3 g of silane coupling agent KH-560 and 50 mL of ethanol solution with a volume fraction of 85% were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 400 r / min, and then added and heated to reflux and continued to stir for 3 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 3 h to obtain organosilicon modified carbon fiber;

[0036] Step T5: 5 g of organosilicon-modified carbon fiber, 0.3 g of benzyltriethylammonium chloride, 2.5 g of citric acid and 70 mL of deionized water were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 400 r / min, and then added and heated to reflux and continued to stir for 6 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 40 ° C for 5 h to obtain a multi-group modified carbon fiber;

[0037] Step T6: Weigh 27 parts of iron powder, 22 parts of nickel powder, 11 parts of chromium powder, 7 parts of multi-group modified carbon fiber, 5 parts of rutile, 4 parts of molybdenum powder, 3 parts of marble and 1 part of titanium dioxide according to weight parts, and set aside;

[0038] Step T7: uniformly mixing iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0039] Step T8: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:6, and ball milling for 3 hours at a ball milling rate of 400 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0040] Step T9: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0041] Step T10: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0042] Embodiment 2:

[0043] This embodiment is a method for preparing a tough self-shielded flux-cored welding wire, comprising the following steps:

[0044] Step T1: 5 g of carbon fiber with a length of 3 mm and a diameter of 5 μm was added to 62 mL of anhydrous ethanol, and then ultrasonically dispersed for 9 hours under an ultrasonic power of 325 W, and then vacuum filtered. The filter cake was added to a three-necked flask equipped with a thermometer and a stirrer, and then 62 mL of a sodium hydroxide solution with a mass fraction of 12% was added and stirred for 1.2 hours at a temperature of 62 ° C and a stirring rate of 450 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 92 ° C for 2.5 hours to obtain pretreated carbon fiber;

[0045] Step T2: 2 g of pretreated carbon fiber, 10.5 g of glucose and 52 mL of deionized water were added to a three-necked flask equipped with a thermometer and a stirrer, and then stirred for 12 h at a temperature of 38 ° C and a stirring rate of 450 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 92 ° C for 11 h to obtain soaked carbon fiber;

[0046] Step T3: 2g soaked carbon fiber, 6.8g silicon powder, 0.55g nickel nitrate powder and 0.55g ferric chloride powder were mixed evenly, and then added to a graphite crucible, and then placed in a tubular furnace, argon protection was introduced, and sintered at a temperature of 1450°C for 1.2h, and then cooled with the furnace, and then added to distilled water, and then ultrasonically dispersed for 25min at an ultrasonic power of 325W, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven, and dried at a temperature of 82°C for 4.5h to obtain silicon carbide coated carbon fiber;

[0047] Step T4: 2 g of silicon carbide coated carbon fiber, 2.6 g of silane coupling agent KH-560 and 52 mL of ethanol solution with a volume fraction of 88% were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 450 r / min, and then added and heated to reflux and continued to stir for 4 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 4 h to obtain organosilicon modified carbon fiber;

[0048] Step T5: 5 g of organosilicon-modified carbon fiber, 0.6 g of benzyltriethylammonium chloride, 3.7 g of citric acid and 75 mL of deionized water were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 450 r / min, and then added and heated to reflux and continued to stir for 7 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed 4 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 42 ° C for 5.5 h to obtain a multi-group modified carbon fiber;

[0049] Step T6: weigh 30 parts of iron powder, 25 parts of nickel powder, 14 parts of chromium powder, 13 parts of multi-group modified carbon fiber, 8 parts of rutile, 6 parts of molybdenum powder, 5 parts of marble and 3 parts of titanium dioxide according to weight parts, and set aside;

[0050] Step T7: uniformly mixing iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0051] Step T8: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:7, and ball milling for 4 hours at a ball milling rate of 450 r / min to obtain a ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0052] Step T9: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0053] Step T10: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0054] Embodiment 3:

[0055] This embodiment is a method for preparing a tough self-shielded flux-cored welding wire, comprising the following steps:

[0056] Step T1: 5 g of carbon fiber with a length of 3 mm and a diameter of 5 μm was added to 65 mL of anhydrous ethanol, and then ultrasonically dispersed for 10 h under an ultrasonic power of 350 W, and then vacuum filtered. The filter cake was added to a three-necked flask equipped with a thermometer and a stirrer, and then 65 mL of a sodium hydroxide solution with a mass fraction of 15% was added and stirred for 1.5 h at a temperature of 65 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 95 ° C for 3 h to obtain pretreated carbon fiber;

[0057] Step T2: 2 g of pretreated carbon fiber, 12 g of glucose and 55 mL of deionized water were added to a three-necked flask equipped with a thermometer and a stirrer, and then stirred for 15 h at a temperature of 40 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 95 ° C for 12 h to obtain soaked carbon fiber;

[0058] Step T3: 2g soaked carbon fiber, 7g silicon powder, 0.6g nickel nitrate powder and 0.6g ferric chloride powder were mixed evenly, and then added to a graphite crucible, and then placed in a tubular furnace, argon protection was introduced, and sintered at a temperature of 1500°C for 1.5h, and then cooled with the furnace, and then added to distilled water, and then ultrasonically dispersed for 30min under an ultrasonic power of 350W, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven, and dried at a temperature of 85°C for 5h to obtain silicon carbide coated carbon fiber;

[0059] Step T4: 2 g of silicon carbide coated carbon fiber, 3.9 g of silane coupling agent KH-560 and 55 mL of 90% ethanol solution by volume were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 500 r / min, and then added and heated to reflux and continued to stir for 5 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain silicone modified carbon fiber;

[0060] Step T5: 5 g of organosilicon-modified carbon fiber, 0.9 g of benzyltriethylammonium chloride, 4.9 g of citric acid and 80 mL of deionized water were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 500 r / min, and then added and heated to reflux and continued to stir for 8 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 45 ° C for 6 h to obtain a multi-group modified carbon fiber;

[0061] Step T6: weigh 33 parts of iron powder, 28 parts of nickel powder, 17 parts of chromium powder, 19 parts of multi-group modified carbon fiber, 11 parts of rutile, 8 parts of molybdenum powder, 7 parts of marble and 5 parts of titanium dioxide according to weight parts, and set aside;

[0062] Step T7: uniformly mixing iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0063] Step T8: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:8, and ball milling for 5 hours at a ball milling rate of 500 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0064] Step T9: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0065] Step T10: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0066] Comparative Example 1:

[0067] This comparative example is a method for preparing a strong and tough self-shielded flux-cored welding wire, comprising the following steps:

[0068] Step T1: weigh 33 parts of iron powder, 28 parts of nickel powder, 17 parts of chromium powder, 11 parts of rutile, 8 parts of molybdenum powder, 7 parts of marble and 5 parts of titanium dioxide according to weight parts, and set aside;

[0069] Step T2: Evenly mix iron powder, nickel powder, chromium powder, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0070] Step T3: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:8, and ball milling for 5 hours at a ball milling rate of 500 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0071] Step T4: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0072] Step T5: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0073] Comparative Example 2:

[0074] This comparative example is a method for preparing a strong and tough self-shielded flux-cored welding wire, comprising the following steps:

[0075] Step T1: Weigh 33 parts of iron powder, 28 parts of nickel powder, 17 parts of chromium powder, 19 parts of carbon fiber with a length of 3 mm and a diameter of 5 μm, 11 parts of rutile, 8 parts of molybdenum powder, 7 parts of marble and 5 parts of titanium dioxide according to weight parts, and set aside;

[0076] Step T2: Evenly mix iron powder, nickel powder, chromium powder, carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0077] Step T3: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:8, and ball milling for 5 hours at a ball milling rate of 500 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0078] Step T4: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0079] Step T5: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0080] Comparative Example 3:

[0081] This comparative example is a method for preparing a strong and tough self-shielded flux-cored welding wire, comprising the following steps:

[0082] Step T1: 5 g of carbon fiber with a length of 3 mm and a diameter of 5 μm was added to 65 mL of anhydrous ethanol, and then ultrasonically dispersed for 10 h under an ultrasonic power of 350 W, and then vacuum filtered. The filter cake was added to a three-necked flask equipped with a thermometer and a stirrer, and then 65 mL of a sodium hydroxide solution with a mass fraction of 15% was added and stirred for 1.5 h at a temperature of 65 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 95 ° C for 3 h to obtain pretreated carbon fiber;

[0083] Step T2: 2 g of pretreated carbon fiber, 12 g of glucose and 55 mL of deionized water were added to a three-necked flask equipped with a thermometer and a stirrer, and then stirred for 15 h at a temperature of 40 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 95 ° C for 12 h to obtain soaked carbon fiber;

[0084] Step T3: 2g soaked carbon fiber, 7g silicon powder, 0.6g nickel nitrate powder and 0.6g ferric chloride powder were mixed evenly, and then added to a graphite crucible, and then placed in a tubular furnace, argon protection was introduced, and sintered at a temperature of 1500°C for 1.5h, and then cooled with the furnace, and then added to distilled water, and then ultrasonically dispersed for 30min under an ultrasonic power of 350W, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven, and dried at a temperature of 85°C for 5h to obtain silicon carbide coated carbon fiber;

[0085] Step T4: 33 parts of iron powder, 28 parts of nickel powder, 17 parts of chromium powder, 19 parts of silicon carbide coated carbon fiber, 11 parts of rutile, 8 parts of molybdenum powder, 7 parts of marble and 5 parts of titanium dioxide were weighed according to weight and set aside;

[0086] Step T5: uniformly mixing iron powder, nickel powder, chromium powder, silicon carbide coated carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0087] Step T6: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:8, and ball milling for 5 hours at a ball milling rate of 500 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0088] Step T7: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0089] Step T8: Fill the U-shaped steel strip with welding wire powder at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0090] Comparative Example 4:

[0091] This comparative example is a method for preparing a strong and tough self-shielded flux-cored welding wire, comprising the following steps:

[0092] Step T1: 5 g of carbon fiber with a length of 3 mm and a diameter of 5 μm was added to 65 mL of anhydrous ethanol, and then ultrasonically dispersed for 10 h under an ultrasonic power of 350 W, and then vacuum filtered. The filter cake was added to a three-necked flask equipped with a thermometer and a stirrer, and then 65 mL of a sodium hydroxide solution with a mass fraction of 15% was added and stirred for 1.5 h at a temperature of 65 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 95 ° C for 3 h to obtain pretreated carbon fiber;

[0093] Step T2: 2 g of pretreated carbon fiber, 12 g of glucose and 55 mL of deionized water were added to a three-necked flask equipped with a thermometer and a stirrer, and then stirred for 15 h at a temperature of 40 ° C and a stirring rate of 500 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 95 ° C for 12 h to obtain soaked carbon fiber;

[0094] Step T3: 2g soaked carbon fiber, 7g silicon powder, 0.6g nickel nitrate powder and 0.6g ferric chloride powder were mixed evenly, and then added to a graphite crucible, and then placed in a tubular furnace, argon protection was introduced, and sintered at a temperature of 1500°C for 1.5h, and then cooled with the furnace, and then added to distilled water, and then ultrasonically dispersed for 30min under an ultrasonic power of 350W, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven, and dried at a temperature of 85°C for 5h to obtain silicon carbide coated carbon fiber;

[0095] Step T4: 2 g of silicon carbide coated carbon fiber, 3.9 g of silane coupling agent KH-560 and 55 mL of 90% ethanol solution by volume were added to a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 500 r / min, and then added and heated to reflux and continued to stir for 5 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain silicone modified carbon fiber;

[0096] Step T5: weigh 33 parts of iron powder, 28 parts of nickel powder, 17 parts of chromium powder, 19 parts of organosilicon-modified carbon fiber, 11 parts of rutile, 8 parts of molybdenum powder, 7 parts of marble and 5 parts of titanium dioxide according to weight parts, and set aside;

[0097] Step T6: uniformly mixing iron powder, nickel powder, chromium powder, organosilicon-modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain a mixed powder;

[0098] Step T7: adding the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:8, and ball milling for 5 hours at a ball milling rate of 500 r / min to obtain ball milling slurry, and spray drying the ball milling slurry to obtain welding wire powder;

[0099] Step T8: rolling a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bending it into a "U" shape to obtain a U-shaped steel strip;

[0100] Step T9: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

[0101] The tough self-shielded flux-cored welding wires of Examples 1-3 and Comparative Examples 1-4 were welded using a Tribet NBC200 welding machine at a welding voltage of 18-20 V and a welding current of 130-150 A. After welding, the mechanical properties of the welded joints were tested. The test results are shown in the following table:

[0102]

[0103] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that adding carbon fiber, silicon carbide coated carbon fiber, organosilicon modified carbon fiber and multi-group modified carbon fiber can effectively improve the mechanical properties of flux-cored welding wire, among which the reinforcing effect of multi-group modified carbon fiber is the most obvious.

[0104] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0105] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A strong and tough self-shielded flux-cored welding wire, characterized in that: Including welding wire powder; Wherein, the welding wire powder comprises the following components in parts by weight: 27-33 parts of iron powder, 22-28 parts of nickel powder, 11-17 parts of chromium powder, 7-19 parts of multi-group modified carbon fiber, 5-11 parts of rutile, 4-8 parts of molybdenum powder, 3-7 parts of marble and 1-5 parts of titanium dioxide; Wherein, the multi-group modified carbon fiber is prepared by the following steps: Step s1: adding carbon fiber to anhydrous ethanol for ultrasonic dispersion, followed by vacuum filtration, stirring the filter cake and sodium hydroxide solution for reaction, cooling the reaction product after the reaction is completed, followed by vacuum filtration, washing and drying the filter cake to obtain pretreated carbon fiber; Step s2: stirring the pretreated carbon fiber, glucose and deionized water to react, cooling the reaction product after the reaction is completed, and then vacuum filtering and drying the filter cake to obtain soaked carbon fiber; Step s3: Evenly mix the soaked carbon fiber, silicon powder, nickel nitrate powder and ferric chloride powder, then sinter, then cool with the furnace, add to distilled water for ultrasonic dispersion, then vacuum filter, dry the filter cake to obtain silicon carbide coated carbon fiber; Step s4: stirring the silicon carbide coated carbon fiber, the silane coupling agent KH-560 and the ethanol solution to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain the organosilicon modified carbon fiber; Step s5: stirring the organosilicon-modified carbon fiber, benzyltriethylammonium chloride, citric acid and deionized water for reaction, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain multi-group modified carbon fiber.

2. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The usage ratio of the carbon fiber, anhydrous ethanol and sodium hydroxide solution in step s1 is 5g:60-65mL:60-65mL.

3. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The carbon fiber in step s1 has a length of 3 mm and a diameter of 5 μm, and the mass fraction of the sodium hydroxide solution is 10-15%.

4. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The dosage ratio of the pretreated carbon fiber, glucose and deionized water in step s2 is 2g:9-12g:50-55mL.

5. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The usage ratio of the soaked carbon fiber, silicon powder, nickel nitrate powder and ferric chloride powder in step s3 is 2g:6.5-7g:0.5-0.6g:0.5-0.6g.

6. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The amount ratio of the silicon carbide coated carbon fiber, the silane coupling agent KH-560 and the ethanol solution in step s4 is 2g:1.3-3.9g:50-55mL.

7. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The volume fraction of the ethanol solution in step s4 is 85-90%.

8. A tough self-shielded flux-cored welding wire according to claim 1, characterized in that: The usage ratio of the organosilicon-modified carbon fiber, benzyltriethylammonium chloride, citric acid and deionized water in step s5 is 5 g: 0.3-0.9 g: 2.5-4.9 g: 70-80 mL.

9. A method for preparing a tough self-shielded flux-cored welding wire as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Evenly mix iron powder, nickel powder, chromium powder, multi-group modified carbon fiber, rutile, molybdenum powder, marble and titanium dioxide to obtain mixed powder; Step 2: Add the mixed powder and anhydrous ethanol into a ball mill at a mass ratio of 1:6-8, and ball mill for 3-5 hours at a ball milling rate of 400-500 r / min to obtain a ball milling slurry, and spray dry the ball milling slurry to obtain welding wire powder; Step 3: Roll a low-carbon steel strip with a width of 10 mm and a thickness of 0.3 mm, and bend it into a "U" shape to obtain a U-shaped steel strip; Step 4: Fill the welding wire powder into the U-shaped steel strip at a filling rate of 25-30%, then close the seal, and draw and reduce the diameter until the diameter is 1.2 mm to obtain the tough self-shielded flux-cored welding wire.

Citation Information

Patent Citations

  • Surfacing method of carbon-doped composite surfacing material

    CN107175388A

  • Self-protection type flux-cored wire for welding of G520 stainless steel and 25Cr2Ni4MoV alloy steel and preparation method of self-protection type flux-cored wire

    CN108356447A